Creativity as a Problem for Moral Theology: John Locke's 99 Percent Challenge to the Catholic Doctrine of Property - Finn, Daniel K. (Horizons, 2000)
According to the classic Catholic doctrine of property, owners who have more than they need are obliged to share their surplus with others who have less than they need. From the patristic era to the work of John Paul II, this obligation has been understood to arise most fundamentally from the character of the objects owned: the material world is a gift from the Creator, intended to meet the needs of all humanity. Three centuries ago, John Locke argued that 99 percent of the value of modern wealth is attributable not to natural resources but to human labor and invention, implicitly restricting the classic obligations of property owners to a mere 1 percent of wealth. Catholic moral theology has yet to integrate Locke's insight about human creativity and economic productivity into an adequate doctrine of property. This article surveys the problem and provides an outline of a constructive response.